NEGOTIATING THE SACRED: Rajah, Orthodoxy, and the Digital Reframing of Islamic Symbol - Zaki, Muhammad Satrio Wibowo; Zamzami, Mukhammad (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2025)
The phenomenon of the rajah as an Islamic talisman occupies a contested discursive space between theological legitimacy and strong condemnation as a practice of shirk. This debate is rooted in the diversity of the Prophet’s hadith, which, on the one hand, allows ruqyah as long as it is free from elements of shirk, but on the other hand, categorically condemns all forms of talismans. Whereas previously the relevant authority of the rajah was determined through fatwas issued by religious scholars and local religious practices, now the discourse has shifted to the digital realm, mainly through memes and educational content that represent sacred symbols in the form of criticism, satire, and esoteric narratives. This article employs a netnographic approach to discuss the construction of meaning of the rajah in memes on social media and netizens’ responses to them, while also analyzing them from the perspective of hadith interpretation. The study argues that netizen involvement does not stop at spontaneous reactions, but forms a continuum of discourse: from humorous deconstruction to firm normative affirmation, then continuing to historical-esoteric interpretations. These findings confirm that rajah in the digital public sphere is a locus of popular theology that negotiates Islamic orthodoxy, local traditions, and contemporary digital culture.